Producing video podcasts : a guide for media professionals. - Harrington, Richard, 1972-; Weiser, Mark, ....- (Amsterdam : Elsevier, 2008)
Put the video podcast medium to work for you and your clients with a winning formula. Know how video podcasts work and every facet of what it takes to produce a professional-quality program that will meet every criterion for success. The authors are seasoned video production pros that have been on the crest of the video podcasting wave as it has risen. With over 2500 episodes produced, they can reveal what works and what doesnt with detailed, illustrated guidance. You get the nuts and bolts of the complete process, including: * Preproduction: budgeting guidelines, mapping your production, and working with talent * Production: the ENG shooting style, lighting values and portability, sound, essential camera features, acquisition formats, and gear lists * Postproduction: resources for adding music and images, motion graphics, and editing techniques * Delivery: cost-effective hosting options, creating RSS feeds, compression, and hosting processes * Promotion: choosing directories, promoting your program, and monetizing your podcast Instruction and case studies go in-depth on issues unique to the podcast medium. A full-color presentation delivers tangible, inspiring examples of creative video podcasts. The companion websitewww.VidPodcaster.comprovides a blog, templates, planning documents, sample clips, and state-of-the-art updates. * Written by video experts for video experts * Artist profiles and case studies demonstrate creative implementations * Companion web site provides template planning documents, sample clips and state-of-the-art updates